Drag and added mass coefficients of a flexible pipe undergoing vortex-induced vibration in an oscillatory flow. (15th August 2020) - Ren, Haojie; Zhang, Mengmeng; Wang, Yifan; Xu, Yuwang; Fu, Shixiao; Fu, Xuepeng; Zhao, Bing
Abstract: The drag and added mass coefficients of a flexible pipe undergoing vortex-induced vibration (VIV) in an oscillatory flow are investigated experimentally with maximum reduced velocities ranging from 4 to 7.9 and Keulegan-Carpenter (KC) numbers ranging from 10 to 178. The strain responses are measured by fiber bragg grating sensors. By using displacement reconstruction and inverse analysis methods, displacement response and hydrodynamic force are identified. Then, through least square method, drag and added mass coefficients are extracted. The results show that drag coefficient varies with both the maximum reduced velocity and KC number. It is stable in cases with large KC numbers but significantly amplified in the cases of small KC numbers. The maximum value of the drag coefficient can reach 3.5 at kC < 30. A comparison with the results of a stationary cylinder without VIV in an oscillatory flow demonstrates that VIV can amplify the drag coefficient and reduce the sensitivity of the hydrodynamic coefficients to the Stokes number. Based on the experimental results, an empirical formula for predicting the drag coefficients in an oscillatory flow is proposed that accounts for the VIV response and KC number, and its applicability is effectively verified via a comparison between the predicted and experimental results. Highlights: The hydrodynamics of flexible pipe in an oscillatory flow are first revealed. Drag coefficients magnification under small KC numbers in an oscillatory flow was observed. VIV can reduce the sensitivity of the hydrodynamic coefficients to the Stokes number. An empirical mean drag coefficient prediction formula for a flexible pipe in an oscillatory flow is proposed.